Influence of cold gas spray parameters on the corrosion resistance of Al-Al2O3 coatings sprayed on carbon steel - da Silva, F. S. [UNESP]; Cinca, N.; Dosta, S.; Cano, I. G.; Guilemany, J. M.; Benedetti, A. V. [UNESP] (SAGE Publications, 2019)
This work describes the influence of standoff distance (SoD), and gas temperature on the morphology and corrosion resistance of Al-10%Al2O3 coatings deposited by cold gas spray (CGS) on carbon steel. The results showed that the standoff distance had little effect on the thickness and microstructure of the coating. However, a 100 °C decrease of the spraying temperature reduced the coating thickness by 300 µm. The use of electrochemical analyses and SEM images showed that all the coatings studied were able to protect the substrate during at least 1300 h of immersion, due to the dense microstructure obtained by CGS.
Keywords: Al-Al2O3; cold gas spray; composite; Reinforced coatings